2015
DOI: 10.1007/s00222-015-0638-0
|View full text |Cite
|
Sign up to set email alerts
|

Ground states are generically a periodic orbit

Abstract: Abstract. We prove that for an expanding transformation the maximizing measures of a generic Lipschitz function are supported on a single periodic orbit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 22 publications
1
65
0
2
Order By: Relevance
“…6 In dimension d = 1, Brémont showed that there is no finite-range interaction that is chaotic, see [7] and also [8,16,22]. See also [3,5,11,17] and the monograph [4] for recent related results.…”
Section: Symbolic Spacementioning
confidence: 96%
“…6 In dimension d = 1, Brémont showed that there is no finite-range interaction that is chaotic, see [7] and also [8,16,22]. See also [3,5,11,17] and the monograph [4] for recent related results.…”
Section: Symbolic Spacementioning
confidence: 96%
“…C 1 ) functions on X, though the case V = Lip was discussed in more detail. In subsequent years this case V = Lip became a focus of attention among workers in ergodic optimization, culminating in its resolution (see Theorem 7.10 below) by Contreras [50], building on work of [125,141,159].…”
Section: Typically Periodic Optimization (Tpo)mentioning
confidence: 99%
“…16 Condition (16) was introduced by Yuan & Hunt [159, p. 1217], who called it the Class I condition. (A Class II condition was also introduced in [159], in terms of approximability by periodic orbit measures, which stimulated related work in [42,49] [50] showed, by estimating the lengths of pseudo-orbits, that if µ ∈ M T \ M Y H then µ has strictly positive entropy. However, a result of Morris [125] asserts that the set of Lipschitz functions with a positive entropy maximizing measure is of first category; it follows that Lip \ Lip Y H is of first category, and therefore Lip Y H is dense in Lip, as required.…”
Section: Typically Periodic Optimization (Tpo)mentioning
confidence: 99%
“…Some examples of this are [9,7,6,5,3,10,11]. A good introduction to the subject is [8], where the fundamental results of the theory are displayed and recentelly, in [4] an important conjecture was proved.…”
Section: Introductionmentioning
confidence: 99%